AB0527 Hla-b27 analysis by flow citometry in brazilian patients with ankylosing spondylitis and psoriatic arthritis. (23rd January 2014) - Goldenstein-Schainberg, C.; Carrasco, S.; Saad, C.; Goncalves, C.; Sampaio-Barros, P.; Parra, E.
Abstract : Background: Ankylosing spondylitis (AS) and psoriatic arthritis (PsA) share common characteristics including the association with HLA-B27 antigen, which is positive in > 80% and 20-60% patients respectively and mostly related to axial involvement. Considerable geographical HLA-B27 prevalence in general population varies from > 50% in Canadian Indians and virtually 0% in Africans. HLAB27 may be detected by a variety of methods with similar sensibility and specificity, but different cost including serological (luminex system, solid phase assay), ADCC, molecular biology (PCR) and flow cytometry. Objectives: To establish the prevalence of HLA-B27 in Brazilian patients with AS and PsA from a single university center using a low cost flow cytometry test. Methods: AS and PsA patients followed at theEpA clinic from the Rheumatology Division of the Hospital das Clinicas, University of São Paulo were evaluated. HLA-B27 was analyzed in peripheral blood lymphocytes by flow cytometry using the FacsCalibur Becton/Dinkinson (BD). Fifty µl of heparinizedwhole blood from all patients and controls were incubated with 30µl HLA-B27/CD3 antibody (BD) for 30 minutes in the dark followed by red cell lysis with 2ml of lysis solution (BD). All samples were washed twice with PBS and fixed with 250µl of 1% paraformaldehyde. Statistical analysis was performed using Fisher's test and P<0.005 was considered significant. Results: A total of 182 patients (88 AS, 94 PsA) and 72 controls were studied. Axial involvement occurred in 97% AS and 50% PsA patients, whereas 63% AS and 89% PsA had peripheral disease. HLA-B27 was positive in 83% (73/88) AS, 33% (31/94) PsA and 2.7% (2/72) controls. In AS, HLA-B27+ was associated with axial but not peripheral involvement (96%, 70/73 vs61%, 45/73, p = 0.047). Conversely, HLA-B27 was positive in 90% (28/31) peripheral PsA vs. 55% (17/31) axial PsA patients ( p =0.003) Conclusions: The detection of HLA-B27 by flow cytometry in Brazilian patients with AS and PsA was similar to worldwide reported prevalences proving to be a reliable inexpensive method. In AS, HLA-B27 association with axial manifestation was confirmed but in PSA, link with peripheral disease may suggest different patterns of site injury indicating that HLA-B27 testing is of little clinical value in predicting the presence of axial PsA. Disclosure of Interest: None Declared